The following can be deduced from the expressions
m ∠ D = 4 × m ∠ A
m ∠ B = 3 × m ∠ A-12
Please note that the sum of angles in a triangle is 180 degress. Therefore,
M∠ A + m ∠ B + m ∠ D = 180equation(3)
Substitute for equation 1 and 2 in equation 3 as shown below
m ∠ A + 3 × m ∠ A - 12^0 + 4 x m ∠ A =180^0
m ∠ A + 3 × m ∠ A + 4 x m ∠ A = 180^0+12^0
8m ∠ A = 192^0
m ∠ A= 192^0/8
m ∠ A=24^0
Substitute for m∠A= 24 in equation 1 and 2 as shown below
m ∠ D = 4 × m ∠ A
m ∠ D = 4 × 24^0
m ∠ D = 96^0
m ∠ B = 3 × mA - 12^0
m ∠ B = 3 × 24^0 - 12
m ∠ B = 72^0 - 12^0
,
∠= °
∠= °
∠= °